Impact of Social Media and Digital Innovation in Business Models: Strategies that Leverage Dynamic Capabilities - Zainul Wasik; S. Sudarnice Sudarnice; Dedy Iswanto; Lia Febria lina (PT. Mawadaku Sukses Solusindo, 2024)
Modern digital technology has enabled many businesses, includes family-run enterprises, to develop novel business strategies. We investigate how dynamic capacity functions as a mediator in the connection between creativity and social impact of the business model of the digital age (BMI), as well as the role of environmental dynamics moderator. We demonstrate the beneficial correlation between family damage and digital BMI through utilizing unique survey data from 1,444 Indonesian businesses with and without family damage, this study examines knowledge exploitation, risk management, and marketing capabilities. As a result of this, and in opposition to our assumptions, we recognize that positive relationships between the group's interests and its dynamic capabilities are strengthened by the environment. All of us bear significant ramifications for digital BMI research and family business innovation, both of which shed light on the dynamics of dynamic ecosystems in the digital economy.